2015
DOI: 10.1071/ch14606
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine with cis-9,trans-11 and trans-10,cis-12 Conjugated Linoleic Acid Isomers: Synthesis and Cytotoxic Studies

Abstract: Novel phosphatidylcholines and lysophosphatidylcholines with cis-9,trans-11 and trans-10,cis-12 conjugated linoleic acid (CLA) were synthesized in high yields (75-99 %). The in vitro cytotoxic activities of these compounds against three human cancer cell lines (HL-60, MCF-7, and HT-29) were evaluated. The results revealed that there are differences in the activity between phosphatidylcholine with cis-9,trans-11 and trans-10,cis-12 CLA acyl groups. 1,2-Di(9Z,11E)octadecadienoyl-sn-glycero-3-phosphocholine was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Hydrolysis of 1,2-dipalmitoyl- sn -glycero-3-phosphocholine ( 5 ) was carried out according to the method described by Morgado et al [ 21 ]. The detailed data were described earlier [ 22 ]. 1-Palmitoyl-2-hydroxy- sn -glycero-3-phosphocholine (6) was obtained in 99% yield and its physical and spectroscopic data were consistent with those found in literature [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hydrolysis of 1,2-dipalmitoyl- sn -glycero-3-phosphocholine ( 5 ) was carried out according to the method described by Morgado et al [ 21 ]. The detailed data were described earlier [ 22 ]. 1-Palmitoyl-2-hydroxy- sn -glycero-3-phosphocholine (6) was obtained in 99% yield and its physical and spectroscopic data were consistent with those found in literature [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mono-and digalactosyldiacylglycerols also play roles in the regulation of systemic acquired resistance in plants (Gao et al, 2014). Perhaps the best candidate to explain the decreased herbivore performance is the linoleoyl lysophosphocholine, as some compounds in this class have been shown to be highly cytotoxic to human cancer cell lines (Niezgoda et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…1II), since such esters react faster than acids. For the reduction an Data derived from earlier experiment [29]. equivalent of LAH in anhydrous diethyl ether was used and the reaction was conducted at room temperature.…”
Section: Chemical Synthesis Of Fatty Acid Derivativesmentioning
confidence: 99%
“…Also phospholipids can be used as an alternative carriers for conjugated linoleic acid. Recently we developed chemical and enzymatic methods for effective synthesis of phosphatidylcholine with conjugated linoleic acid isomers . Studies have shown that supplementation of essential fatty acids in the form of phosphatidylcholines and ethyl esters were more effective than in the TAG form or free fatty acids itself .…”
Section: Introductionmentioning
confidence: 99%